2023
DOI: 10.1253/circj.cj-22-0252
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Development of Thrombosis and Worsening of Disease Severity in Patients With Moderate COVID-19 on Admission ― From the CLOT-COVID Study ―

Abstract: Background:The worsening of coronavirus disease 2019 (COVID-19) severity is a critical issue in current clinical settings and may be associated with the development of thrombosis. Methods and Results:This study used patient data obtained in the CLOT-COVID study, a retrospective multicenter cohort study. The demographics of patients with moderate COVID-19 on admission with and without worsened severity during hospitalization were compared and predictors were identified. Of 927 patients with moderate COVID-19 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This physician-initiated, observational cohort study involved the analysis of data accumulated in the nationwide “The Thrombosis and Anticoagulation Therapy in patients with COVID-19 in Japan Study” (CLOT-COVID Study; UMIN000045800), which enrolled consecutive hospitalized COVID-19 patients from April to September 2021 in 16 centers in Japan. 18 22 The primary objective of the CLOT-COVID study was to reveal the current status of thrombosis and anticoagulation therapy in patients with COVID-19 in Japan. 18 Patients with COVID-19 confirmed by polymerase chain reaction were eligible for inclusion.…”
Section: Methodsmentioning
confidence: 99%
“…This physician-initiated, observational cohort study involved the analysis of data accumulated in the nationwide “The Thrombosis and Anticoagulation Therapy in patients with COVID-19 in Japan Study” (CLOT-COVID Study; UMIN000045800), which enrolled consecutive hospitalized COVID-19 patients from April to September 2021 in 16 centers in Japan. 18 22 The primary objective of the CLOT-COVID study was to reveal the current status of thrombosis and anticoagulation therapy in patients with COVID-19 in Japan. 18 Patients with COVID-19 confirmed by polymerase chain reaction were eligible for inclusion.…”
Section: Methodsmentioning
confidence: 99%
“…To elucidate the detailed status of thrombosis, including VTE, in Japan, a multicenter retrospective cohort study was conducted to investigate the incidence and clinical features of VTE among hospitalized COVID-19 patients who underwent contrast-enhanced computed tomography (CECT) during hospitalization at 22 The optimal intensity of anticoagulation therapy for COVID-19 according to its severity might also be a big issue in Japan, although it has been investigated in a number of previous clinical trials, mainly in the Caucasian population. As for the anticoagulation therapy for moderately ill patients with COVID-19, a previous study showed that approximately 20% of patients with moderate COVID-19 experienced worsened severity during hospitalization with which increased age, diabetes, D-dimer levels >1.0 µg/mL on admission, and the development of thrombosis during hospitalization were significantly associated 63) . These results indicated that a more aggressive pharmacological thromboprophylaxis might be helpful for the prevention of worsening COVID-19 severity among high-risk patients.…”
Section: Covid-19-related Thrombosis In Japanmentioning
confidence: 99%
“… 9 ) Thrombus development was associated with COVID-19 severity, and bleeding risk was related to COVID-19 severity and anticoagulation but not with age. 10 12 )…”
Section: Introductionmentioning
confidence: 99%
“…9) Thrombus development was associated with COVID-19 severity, and bleeding risk was related to COVID-19 severity and anticoagulation but not with age. [10][11][12] In patients with COVID-19, VTE, particularly pulmonary embolism (PE), may be a major cause of thrombosis. [13][14][15] However, there has been limited data on the detailed types of thrombosis, which could be important for understanding thrombosis associated with COVID-19.…”
Section: Introductionmentioning
confidence: 99%